PHYSICO-CHEMICAL CHANGES IN UHT TREATED AND WHOLE MILK POWDER DURING STORAGE AT AMBIENT TEMPERATURE - Akhtar, Saeed; Zahoor, Tahir; Hashmi, Abdul Moeed (Journal of Research (Science), 2003)
We studied the changes in pH, acidity and viscosity of ultra high temperature (UHT) treated and reconstituted whole milk powder (WMP) during storage of 90 days at room temperature. The samples were analyzed at 0, 30, 60 and 90 days intervals for these physico - chemical properties of the milk types. Values indicated an increase in acidity and viscosity with a decrease in pH with the storage time increased both in UHT treated and reconstituted whole milk powder. Apart from many enzymatic changes to deteriorate the milk, these apparent changes in milk characteristics may be one of the reasons that UHT milk cannot be kept unspoiled above 90 days and the quality of WMP is influenced within this time period.